Analysis of the Attitudes of Coastal Communities in Sasi Management in Leihitu District, Central Maluku Regency - Henderika Litaay, Simona Christina; Agustang, Andi; Syukur, Muhammad (International Journal of Criminology and Sociology, 2022)
Sasi is a belief system, rules, and rituals that involve temporary prohibitions on the use of specific resources or areas. Social, economic-political, and ecological pressures are the background for the dynamics of Sasi. This study aimed to explain the impact of the Attitudes of the Coastal Community on Sasi Management in Leihitu District, Central Maluku Regency. This research used a descriptive qualitative method, and it was conducted in the Leihitu sub-district, Central Maluku district. The research location was selected by purposive sampling. The results showed that most of the coastal communities in the Leihitu sub-district accepted/supported Sasi's implementation. The knowledge about Sasi and communication affects the coast in the Leihitu sub-district, Central Maluku District. At the same time, the closing of the Sasi distinguishes the implementation of Sasi. The opening of the Sasi is carried out by traditional, religious, or a combination. The monitoring, accountability, and enforcement mechanisms carried out in traditional coastal resource management are generally carried out within the community, with the community observing the violations that occur.